2006
DOI: 10.1111/j.1365-3040.2006.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Arabidopsis thermosensitive mutant atts02 reveals an important role for galactolipids in thermotolerance

Abstract: Plants are constantly challenged with various abiotic stresses in their natural environment. Elevated temperatures have a detrimental impact on overall plant growth and productivity. Many plants increase their tolerance to high temperatures through an adaptation response known as acquired thermotolerance. To identify the various mechanisms that plants have evolved to cope with high temperature stress, we have isolated a series of Arabidopsis mutants that are defective in the acquisition of thermotolerance afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 51 publications
(114 reference statements)
12
97
0
Order By: Relevance
“…Under phosphate starvation, phospholipids are replaced by galactolipids in not only the thylakoid membrane, but also the extraplastidic membranes (Härtel et al, 2000), thereby reducing the need for phosphorus consumption for membrane lipid biosynthesis. Proportional changes of glycerolipid species have also been documented in plants subjected to temperature fluctuations (Pearcy, 1978;Johnson and Williams, 1989;Harwood, 1991Harwood, , 1994Chen et al, 2006). An increased proportion of DGDG was observed at high temperature in Arabidopsis (Chen et al, 2006), whereas biosynthesis of MGDG in canola (Brassica napus) was induced by low temperature (Johnson and Williams, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Under phosphate starvation, phospholipids are replaced by galactolipids in not only the thylakoid membrane, but also the extraplastidic membranes (Härtel et al, 2000), thereby reducing the need for phosphorus consumption for membrane lipid biosynthesis. Proportional changes of glycerolipid species have also been documented in plants subjected to temperature fluctuations (Pearcy, 1978;Johnson and Williams, 1989;Harwood, 1991Harwood, , 1994Chen et al, 2006). An increased proportion of DGDG was observed at high temperature in Arabidopsis (Chen et al, 2006), whereas biosynthesis of MGDG in canola (Brassica napus) was induced by low temperature (Johnson and Williams, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the saturation level of other major polar lipids in response to heat treatment were also observed in this study (data not shown). Taken together, the results (22) suggest that acquired thermotolerance induced by heat acclimation in wild-type Arabidopsis is associated with an increase in relative amount of GalGalDG, a dramatic increase in GalGalDG to GalDG ratio, and a moderate increase in saturation of fatty acids.…”
Section: Acquired Thermotolerance Induced By Heat Acclimation In Wildmentioning
confidence: 65%
“…DGD1 knock-out mutants also show defective growth phenotypes. In contrast to dgd1-1 and the knockout mutants, the growth and development of dgd1-2 and dgd1-3 mutant plants are similar to wild-type plants under normal conditions (22). To determine if DGD1 function is indeed affected by the mutations in dgd1-2/dgd1-3, their lipid and fatty acid profile changes were examined in comparison to those of wild-type plants under normal growth conditions, using ESI-MS/MS (5, 6).…”
Section: Lipid Changes During Adaptation To Heatmentioning
confidence: 99%
See 1 more Smart Citation
“…How Hsps (or other methods of eliciting thermotolerance discussed in this chapter) can play a role in protecting such important cellular reactions need to be taken up for further research. Chen et al (2006) recently isolated series of Arabidopsis mutants that are defective in the acquisition of thermotolerance in response to sublethal high temperature treatment. In the specific mutant type named dgd1-2 which has lesion with respect to loss of acquired as well as basal thermotolerance, affected gene was shown to encode for digalactosyldiacylglycerol synthase 1 (DGD1).…”
Section: Synthesis To Propose a Modelmentioning
confidence: 99%